Care About The Way You Look? Website Quality Impact on Purchase Decision Mediated by Ewom and Ease of Use - Jean Richard Jokhu (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
In the forthcoming industry of technology, many people look for websites to purchase things online. When people moving to smartphone app there are several app still uses website for their main transaction. One of the benefit of using website is easy to access with smartphone, tablet, laptop, or personal computer. In this research, we try to look for the effect of website quality on a purchase decision in a marketplace and the effect of ease of use and electronic word of mouth as the mediating effect of website on purchase decision. Website quality is examined with the mediating variable as the amplifier toward a purchase decision. An online survey was used to collect respondents (300 valid responses) and PLS was used to analyze the relationship in the structural model. Results suggest that website quality if important in a purchase decision. Second, ease of use and EWOM amplify the effect of website quality on purchase decisions. With excellence website interface and positive online review about the website will increase customer transaction on e-commerce website.